Seed targeting with tiny anti-miR-155 inhibits malignant progression of multiple myeloma cells. (January 2015) - Feng, Maoxiao; Luo, Xiaochuang; Gu, Chunming; Fei, Jia
Abstract Background: miR-155 acts as a ubiquitous oncogene in major classes of human cancers and is a potential target for therapeutic intervention. However, the role of miR-155 in multiple myeloma is poorly understood. Methods: To explore the role of miR-155 in multiple myeloma, we assessed the influence of tiny seed-targeting anti-miR-155 (t-anti-miR-155) on multiple myeloma cell line (RPMI-8266) viability and apoptosis in vitro. Results: t-anti-miR-155 significantly inhibited multiple myeloma cell proliferation, migration, and colony formation. Additionally, t-anti-miR-155 significantly increased CD19 positive cell numbers, which are novel biomarkers for multiple myeloma and suppressor of cytokine signaling 1(SOCS1) was shown to be a target gene for miR-155 in multiple myeloma. Finally, the miR-155 signaling pathway was investigated by KEGG assay. Conclusion: miR-155 in RPMI-8266 cells is a critical oncomiR in multiple myeloma and seed-targeting t-anti-miR-155 might be a novel strategy for miR-155-based therapeutics.